SISTEM INFORMASI PENGENALAN HEWAN BERDASARKAN JENIS MAKANAN BERBASIS MULTIMEDIA INTERAKTIF - Nugraha, Maulana Faridzal Eka; Rostina, Rostina; Kisviantari, Rizkyna Sekar; Rahayu, Trisna Kenti; Febriliana, Miranda Dwi; Fahrezy, Fiqry Fahmy Dwe; Aldo, Dasril (JURSIMA, 2022)
In the current millennial era, technology has developed very rapidly. These developments affect the process of teaching and learning activities, especially elementary schools in terms of the method of delivering material. There are still many schools whose learning methods use blackboards, books, and markers in providing examples of images to their students. Therefore, the quality of the knowledge taught tends to be boring and difficult for students to absorb because the media used by the teacher is less attractive. Many studies have been carried out in the development of interactive multimedia by Kiki Firmantoro, et al (2016), Adi Fitria (2019), Sembiring et al (2018). Based on existing research and development, in this research an interactive learning animation is designed that has a novelty, namely the introduction of animals based on the type of food using the macromedia flash application. This development is equipped with animations such as buttons to connect slides and produce sound effects that are expected to attract children's learning interest. Keywords : interactive multimedia, animal introduction, animation